Strengthening Disaster Literacy through Islamic Religious Education - Narulita, Sari; Rayuna Handawati; Miftahul Jannah (ADPISI (Asosiasi Dosen Pendidikan Agama Islam Se-Indonesia), 2023)
Religious people see disaster as a calamity and destiny that must be faced patiently. The belief that disaster is destiny seems to rule out the possibility of a disaster that can be prevented and minimize its impact. The writing of this article describes the Islamic concept of disaster literacy through a literature study. It also represents its strengthening through the Islamic Religious Education Course, which is a subject that all Muslim students must follow in higher education. By modifying the Islamic and Environmental Concepts material, students are expected to recognize their environment and identify disasters that are prone to occur so that actions can be anticipated to prevent and minimize their impacts.